Effect of Gamma Rays on Some Aspects of BiologicalPerformance of Callosobrchus maculatus (Fabricius)and Trogoderma granarium (Everts). - Baghdad Science Journal (مجلة بغداد للعلوم)
The effect of gamma rays on males and females ofCallasobruchus maculatus and Trogoderma granarium which were irradiated as 1-3 days old adults was investigated. The results revealed that the percent egg hatch for both pests was zero ,and average number of egg (34.2,21.5) for both pests respectively where their males where irradiated with 0.18 kGy and mated with unirradiated females. While the percent of egg hatch and the average number of egg (zero,21,3) respectively when the females where irradiated with 0.18 and 0.15 kGy and mated to unirradiated males for C. maculatus and T. granarium respectively. Furthermore, the results showed that the percent of eggs hatch and average number of egg was ( zero,22.7) for C. maculatus when both sexes irradiated with 0.12 kGy and mated together and it was also (zero,11.5) for T. granarium when both sexes where irradiated with 0.15 kGy and mated together.